Children's screen time and psychosocial symptoms at 5 years of age - the role of parental factors - Janette Niiranen; Olli Kiviruusu; Riitta Vornanen; Anneli Kylliäinen; Outi Saarenpää-Heikkilä; E. Juulia Paavonen (BMC, 2024)
Abstract Background and objectives Electronic media (e-media) has become a universal part of young children's daily lives. Previous studies have found an association between increased screen time and children's psychosocial symptoms. We investigated whether parents' psychological distress and parenting style dimensions explain the association between children's screen time and psychosocial symptoms. Moreover, we investigated whether parents' mental well-being and parenting style dimensions moderate this association. Methods We used data from the Finnish CHILD-SLEEP birth cohort study. Parents and the child were assessed when the child was 5 years old (N = 671). The measure of screen time included program viewing from TV and other devices. Child's psychosocial problems and parents' depression, stress and parenting style dimensions were assessed by self-reports. Results A high level of screen time in children was associated with attention and concentration difficulties, hyperactivity and impulsivity symptoms as well as internalizing and externalizing symptoms among 5-year-olds. For the most part, the associations remained significant despite controlling for parents' mental health, parenting style dimensions and multiple background factors, especially associations relating to attention and concentration difficulties and hyperactivity symptoms were robust. Maternal stress and depression moderated the association between children's screen time and psychosocial symptoms, indicating a more pronounced association among stressed or depressed mothers. Conclusion There is an independent association between children's screen time and psychosocial symptoms which is especially pronounced among those children whose mothers had poorer mental well-being. In clinical practice, the length of screen time should be inquired already at a young age and parents should be offered guidance to reduce the possible ill effects of excessive screen time, as well as help with their own mental health problems.